PENGARUH PENCAMPURAN BEBERAPA JENIS KAYU DAN PERUBAHAN SULFIDITAS PROSES SULFAT TERHADAP SIFAT PENGOLAHAN DAN KUALITAS PULP KAYU KARET - Ridwan A; Pasaribu Pasaribu; Dendi Setyawan; Ina Winarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
One of the plant species which can be cultivated and enables the industrial plantation forest to be established for its timber/wood utilization is rubber trees. In dealing with rubber wood for pulp/paper processing, the residual latexes, despite in small amount, can bring about some nuisances, i.e. the troubles during the cooking, washing, and bleaching, and the appearance of dark pitchspots on the surface of the resulting pulp/paper sheet.Inherent wich such, the main aim of this research was to remove or reduce to some effective degrees the residual latexes from rubber wood pulp cooked using kraft (sulphate) process by regulating the sulfidity of the cooking liquor (20,25,30%), and by mixing rubber wood with four other wood species, i.e. sengon (Paraserianthes falcataria), jabon (Anthocephalus cadamba), tusam (Pinus merkusii Jungh et de Vries), and ekaliptus (Eucalyptus sp.) each with their specific gravity of 0.63, 0.30, 0.52, and 0. 78, respectively.Changes in suljidity from 20 to 30 percent brought about significant decrease in the number of pitchspots, caused by the residual latexes, on the surface of the resulting kraft pulp sheet. Meanwhile, changes in mixture between rubber wood and four other wood species with relative proportion (ovendry weight) from 100:0 to 50:50, and finally to 25:75 brought about also the decrease in the number of pitchspots.In the same occasion, changing the suljidity from 20 to 25 percent caused the increase in breakinglength from 3170 m to 3615 m (increasing by 14.04 percent); tear factor from 97. 776 to 111.100 (increasing by 13.63 percent); and burst factor from 42.913 to 53.623 (increasing by 24.96 percent). However, further changes in sulfidity from 25 percent to 30 percent brought about the decrease in breaking length and burst factor to 3232 m (decreasing by 10.59 percent) and 48.631 (decreasing by 9.31 percent), respectively. In another case, changes in relative proportion of mixture between rubber wood and four other wood species from 100:0 to 25:75 induced the significant increase in burst factor and folding endurance from 44.163 to 54.357 (increasing by 23.08 percent) and from 39.47 to 83.93 (increasing by112.64 percent).